VALIDITY OF DISCOVERY-BASED ETHNOMATEMATICS LESSON PLAN: A DEEP LEARNING APPROACH TO THE PYTHAGOREAN THEOREM - Intan Nurlita; Yurizka Melia Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The lack of integration of local culture into mathematics teaching, which is usually procedural and abstract in nature, is an obstacle to creating valuable, reflective learning experiences that are appropriate for the educational needs of the 21st century. This study aimed to analyze the validity of ethnomathematics-based lesson plan using the Discovery Learning model and Deep Learning approach in the mystery of the Pythagorean Theorem. The methodology applied is research and development (R&D) using a modified 4D model, focusing on the Develop (D3) stage, involving three validators: an expert lecturer in the subject matter and two mathematics teachers from junior high school as implementers. The evaluation instruments consisted of five aspects: content validity, presentation, language use, integration of the learning model, and technical validity. The results of the validation process indicated that the module is highly valid, with Aiken V values ranging from 0.75 to 1.00. This ethnomathematics-based lesson plan with Pythagorean Theorem material successfully links mathematical concepts with local culture, presents an organized and communicative learning structure, and encourages student exploration and reflection very well. These findings confirm that this learning tool is suitable for use in contextual learning of Pythagorean Theorem material. Future researchers are advised to evaluate the effectiveness of this lesson plan through its application in the classroom and to develop similar teaching tools for other materials that are in line with the local context of students.